Gaya Pengambilan Keputusan Kepala Sekolah di SMA Negeri 3 Panyabungan - Reni Septrisia; Siti Fatimah; Alpi Panjaitan; MHD. Yusril Nasution; Mardiana Hapipah (Jurnal Budi Pekerti Agama Islam, 2024)
This research aims to identify and analyze the decision-making style of the principal at SMA Negeri 3 Panyabungan. The research method used is qualitative and based on a case study approach. Data was collected through in-depth interviews, observation and document analysis. This type of research is carried out using data collection techniques in the form of interviews, observation and documentation. The results of the research show: 1) that the principal's decision making style adheres to a rational style, 2) the principal involves related staff, teachers and several representatives of students, 3) obstacles in decision making are often caused by differences of opinion, 4) The solution to facing problem obstacles is to conduct consensus deliberation and take the majority vote. In addition, school principals also show flexibility in adapting their decision-making style according to specific situations and needs, such as when dealing with critical situations or complex problems.